PENGARUH LINGKUNGAN SEKOLAH TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK (STUDI SURVEI DI SMP BINA PANGUDI LUHUR) - NURDIANSYAH, AHMAD FADIL; SUHAIMY, FIRDAUS; PUTRA, MIFTAHUL SYFA; KUNAENIH; ARLIANTI, SARLI AWLIYA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the fact that students’ character formation is not only influenced by the family environment but is also strongly determined by the condition of the school environment. In reality, various character-related problems are still found, including low discipline, lack of responsibility, dishonesty, and a lack of care among students. This study aimed to analyze the influence of the school environment on students’ character formation, to measure the magnitude of its contribution, and to identify efforts to build character through the school environment. This research applied a quantitative approach with a descriptive-correlational design using a cross-sectional method. The population consisted of 186 students of SMP Bina Pangudi Luhur, East Jakarta, while the sample consisted of 65 students determined through the Slovin formula with a 10% margin of error and selected using simple random sampling. Data were obtained through observation, questionnaires, and documentation, then analyzed using the Pearson Product Moment correlation test. The results showed a significance value of 0.000 (< 0.05), so the alternative hypothesis (Ha) was accepted and the null hypothesis (H₀) was rejected. The correlation coefficient (rxy) was 0.784, indicating a strong positive relationship, while the coefficient of determination (R Square) was 0.614, meaning that the school environment contributed 61.4% to students’ character formation, while the remaining 38.6% was influenced by other factors outside this study. Character-building efforts were realized through teachers’ exemplary behavior, habituation of positive conduct, a conducive learning atmosphere, positive teacher-student interaction, and adequate facilities. Therefore, the better the quality of the school environment, the more it will support the successful formation of students’ character.